IMMOBILIZATION OF BACILLUS SP. PROTEASE ON DIFFERENT MATRICES AND ITS ENZYMATIC CHARACTERIZATION - ROOPA PRASAD; A. JAYAKUMARAN NAIR (International Journal of Pharma and Bio Sciences, 2013)
Studies were conducted on the Bacillus sp. neutral protease immobilization on different matrices. The immobilized protease was prepared by three methods, such as entrapment on calcium alginate and gelatin; physical adsorption by celite and alumina; ionic binding by amberlite IR-120 and DEAE-cellulose. The maximum immobilization yield was obtained with celite adsorbed protease. The immobilized enzyme was characterized in comparison with free enzyme. The optimal pH of the immobilized protease was shifted to lower values; and exhibited good thermal stability. The reusability and storage stability of the immobilized enzyme on different carriers was analysed. The ability of Bacillus sp. protease activity even on immobilization and its characteristics could collectively be useful for commercial production.